Election commission and functioning of democracy - Katju, Manjari (2006)
The Election Commission of India is emerging as the fourth important institutional arrangement, the other three being the executive, the legislature and the judiciary. It has also been voted by the people in a country wide poll as the most trusted of all institutions. But the EC need to formulate a conscious policy towards democratisation and rule-enforcement if it has to become the means to the end of a fair and vibrant representative democracy. - Reproduced.
Keywords: Democracy - India; Elections - India; Elections